Fears, Aspirations, and Hopes: A Springboard of Life for Domestically Abused Children - Andacao, Arvin; Lugo, Maria Gloria; Pajo, Danilo (JPAIR Multidisciplinary Research, 2014)
The youth are the hope of the native land. Unfortunately, children in homes where there is domestic violence are more likely to be abused or neglected. This is one of the most prevalent and rampant quandaries in the society which requires critical attention of a victim. Thus, a study was conducted to determine the demographic profile, forge fears, aspirations and hopes as voices of domestically abused children and produce programs to possibly heal the victims. Guided by the qualitative research design and interpretative sociology orientation, the phenomenological approach was primarily used in the study. Information was generated by the researchers through in-depth interview, key informant interview, and focus group discussion utilizing self-made questionnaire. The findings revealed that 90 percent of informants were minor age, all female victims and suffered domestic abuse. The results on the fears, aspirations, and hopes as springboard of their existence showed positive indication with the victims to fulfill their desires. However, government and other support groups were hunted. Hence, the study concludes that aspirations and hopes were constant goal of the victims and their fears were poignant blueprint to their opening or preference of destiny. Further, this study identified various programs needed by the victims to completely attain their aspirations of life.